Depletion of GPSM1 enhances ovarian granulosa cell apoptosis via cAMP-PKA-CREB pathway in vitro - Xuzi Cai; Huijiao Fu; Yan Wang; Qiwen Liu; Xuefeng Wang (BMC, 2020)
Abstract Background Genetic causes of premature ovarian insufficiency (POI) account for approximately 20 ~ 25% of patients. So far, only a few genes have been identified. Results Here, we first identified the c.1840C > A on G-protein signaling modulator 1 (GPSM1) as a susceptibility locus for POI in 10 sporadic POI patients by whole-exome sequencing. The frequency of GPSM1 c.1840C > A was then verified as 3/20 in a POI sample of 20 patients (including the above 10 patients) by Sanger sequencing. RT-PCR and western blot analysis showed the expression of GPSM1 in rat ovaries was increased in the large antral follicle stage compared to the primordial follicle stage (P < 0.01). The cell proliferation assay (CCK8) and flow cytometry suggested that the small-interfering RNA-induced silencing of Gpsm1 significantly increased apoptosis and decreased proliferation of rat ovarian granulosa cells (GCs) (P < 0.01). Furthermore, suppression of Gpsm1 in GCs reduced levels of cAMP, PKAc, p-CREB as well as the ratio of Bcl-2/Bax, and increased the expression of Caspase-3 and Cleaved Caspase-3 (P < 0.01). Conclusions In summary, this study identified a susceptibility variant GPSM1 c.1840C > A of POI for the first time. Gpsm1 was related to rat follicle development, and silencing of Gpsm1 increased apoptosis and decreased proliferation in rat GCs, possibly through inhibition of the cAMP-PKA-CREB pathway.